U.S. Revenue Surprises : Are Happy Days Here to Stay? - Mathai, Koshy (IMF Working Papers; Working Paper, 2007)
A key question for U.S. policymakers is whether the recent strength in federal revenue is likely to continue. This question is addressed through an econometric analysis of the determinants of tax revenue, using time series that are adjusted for tax policy changes. The results suggest that growth in corporate profits and capital gains each contributed forty percent of the increase in the revenue-to-GDP ratio from 2004-2006, and rising income inequality explains much of the rest. While part of the revenue rise is the result of structural changes taking place in the U.S. economy, some of the recent buoyancy is likely to prove temporary, reflecting the highly cyclical nature of these variables.